2019
DOI: 10.1302/0301-620x.101b8.bjj-2018-0963.r1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative surgical risk stratification in osteosarcoma based on the proximity to the major vessels

Abstract: Aims The aim of this study was to determine the risk of local recurrence and survival in patients with osteosarcoma based on the proximity of the tumour to the major vessels. Patients and Methods A total of 226 patients with high-grade non-metastatic osteosarcoma in the limbs were investigated. Median age at diagnosis was 15 years (4 to 67) with the ratio of male to female patients being 1.5:1. The most common site of the tumour was the femur (n = 103) followed by tibia (n = 66). The vascular proximity was cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…One hundred and seven articles were excluded based on the inclusion criteria, while 23 articles were excluded, as they studied the same patient population, estimated from the institution, number of patients and name of the authors. At last, 13 articles met the inclusion criteria and were eligible for analysis [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . Screening and selection details are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One hundred and seven articles were excluded based on the inclusion criteria, while 23 articles were excluded, as they studied the same patient population, estimated from the institution, number of patients and name of the authors. At last, 13 articles met the inclusion criteria and were eligible for analysis [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . Screening and selection details are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We included 12 studies [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [27] analyzing the 5-year overall survival rate in 2826 patients; 1943 patients were treated with LSS and 883 with amputation. The overall pooled analysis demonstrated that the odds of 5-year overall survival was almost 2-fold in patients treated with LSS than those treated with amputation but with substantial heterogeneity (OR: 1.99; 95% CI: 1.35–2.93; I 2 = 74%, p < 0.001) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, surgical margins are associated with the prognosis of malignant bone and soft tissue tumors (24,25). Previous findings demonstrated that the surgical margin is associated with the prognosis of malignant bone and soft tissue tumors in AYA patients (26).…”
Section: Discussionmentioning
confidence: 99%
“…4 High-grade/metastatic osteosarcoma is typically treated with chemotherapy prior to surgical resection if applicable. 5 In localized nonmetastatic disease, the long-term survival is 70%-75% but it drops to only 30% when it is invasive or has metastatic lesions. 6 The use of intraoperative transesophageal echo (TEE) in noncardiac surgery is growing as anesthesiologists have identified other applications and benefits.…”
Section: Introductionmentioning
confidence: 99%